Integrated management of Striga gesnerioides in cowpea using resistant varieties, improved crop nutrition and rhizobium inoculants - Abdullahi, W.M.; Dianda, M.; Boukar, O.; Dieng, I.; Mohammed, G.S.; Belko, N.; Togola, A.; Muhammad, H.; Kanampiu, F.; Giller, Kenneth E.; Vanlauwe, Bernard (Springer, 2022)
Background Cowpea is a grain legume of major importance in sub-Saharan Africa where it is cultivated by smallholder farmers on poor soils and production is often constrained by the parasitic weed Striga gesnerioides.